Solving the geometric firefighter routing problem via integer programming - O. Zambon, Mauricio J.; J. de Rezende, Pedro; C. de Souza, Cid (European journal of operational research, 2019)
•New GFP variants that allow for more general sets of barriers and solutions.•Problems solved to optimality through Integer Programming modeling.•Preprocessing algorithms and IP-based primal heuristics described in detail.•Two large publicly available sets of challenging instances based on actual forests.•Openly accessible best known bounds and solutions for more than a thousand instances. In this paper, we introduce the Geometric Firefighter Routing Problem (gfrp) as a variant of the Geometric Firefighter Problem aiming to better model more realistic situations. We design an exact algorithm based on a core Linear Integer Programming formulation and propose additional sets of valid constraints to strengthen it. The algorithm also includes primal heuristics, and preprocessing procedures to reduce the model size. Besides, we generate two large sets of instances, tailored to the gfrp, and report on comprehensive experimental results for them. Thorough analysis validate the effectiveness of each major step of the algorithm and the overall performance of our approach.